The Red Pony Movie Still - Chas. K. Feldman Group Productions, Incorporated; Republic Pictures; Viacom/Paramount Pictures:::Creator::::::::::::
Tom, aka Jody Tiflin (Peter Miles), Billy Buck (Robert Mitchum), and Fred Tiflin (Shepperd Strudwick) sit around the table having dinner. Alice Tiflin (Myrna Loy) serves coffee to Strudwick. RESTRICTED USE